A wideband millimeter-wave printable antenna on flexible substrate for breast cancer imaging - Islam, Md. Shazzadul; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A.; Hossain, A. K. M. Zakir; Azam, S. M. Kayser (2019)
Breast cancer is the most diagnosed cancer among women all over the world after skin cancer. Meanwhile, electromagnetic imaging has been a prominent detection technique for biomedical diagnosis in recent years. However, the electromagnetic imaging is struggling with the spatial resolution that can be solved by an imaging technique based on the antenna with a wide operating bandwidth at the higher frequency range. In this paper, a printable Coplanar Waveguide (CPW)-fed microstrip rectangular patch antenna with a wide – 10 dB bandwidth of 18.7 GHz has been proposed for a breast cancer imaging application. This printable antenna, after being designed on a flexible substrate and simulated, operates from 21 GHz to 39.7 GHz which covers the millimeter-wave frequencies. The antenna has achieved an average gain of 4 dBi with an average radiation efficiency of over 80% for the entire -10 dB bandwidth. The bidirectional radiation pattern of the antenna offers the freedom of placing the antenna both at the front and back position on the body surface. Moreover, a compact area of 5×5 mm2 makes the antenna suitable for the biomedical imaging application at mm-wave frequencies by utilizing a low-cost manufacturing process.